Biomechanics of fore wing to hind wing coupling in the southern green stink bug Nezara viridula (Pentatomidae). (December 2019) - Ma, Yun; Wan, Chao; Gorb, Stanislav; Rajabi, Hamed
Abstract: Stink bugs have wing coupling mechanisms to synchronize flapping of their wings. The wing coupling is performed through a clamp-like structure on the fore wing (i.e. hemelytron) and a rolled margin on the hind wing. Here we used modern imaging techniques to investigate structural characteristics and material composition of the wing coupling of the stink bug Nezara viridula . We found that the surfaces of the clamp-like structure and the rolled margin are covered by highly-sclerotized microtrichia, which are expected to reduce friction between the wings during flapping flight. Micro-force measurements showed that fore and hind wings can be coupled only in certain angles ranging from 40.6° to 267.7° The results further showed that the force required to uncouple fore and hind wings is maximal for a range of angles which they make with each other during flight (127.1°–238.9°). In contrast to previous observations on some other insect species, the removal of the wing coupling in stink bugs led to complete loss of flight ability. In summary, we concluded that the shape, material composition and orientation of the coupling structure guarantee a robust fore wing to hind wing coupling during flight and a fast, easy uncoupling at rest. Statement of significance: Although the coupling mechanism of insect fore wing and hind wing has long been described, the functionality of this mechanism still remains largely unknown. In the present work, using a combination of modern imaging techniques and mechanical testing, we studied the functional morphology of the fore wing-hind wing coupling mechanism of the stink bug Nezara viridula . Our study reveals the crucial role of the mechanism in the flight ability of the stink bug and sheds light on the structure-property-function relationships of the functional diptery in insects. Graphical abstract: Image, graphical abstract